Microreactor for catalytic partial oxidation of methane - Puwanto, Widodo Wahyu; Muharam, Yuswan (2006)
Fixed-bed reactors for partial oxidation of methane to produce synthetic gas bear a hot-spot problem. To avoid this problem, an alternative reactor, which is called shell and tube type microreactor, has been developed in this work. Combustion and reforming reactions are integrated in this reactor. The microreactor used in this work consists of a 1 cm outsidediameter, 0.8 cm inside-diameter and 11 cm length tube, and a 1.8 cm inside-diameter shell. The tube is made of dense alumina and the shell of quartz. Two different methods ? dip and spray coating ? were performed to coat the tube side with LaNixOy catalyst. Gaseous reactants burn in the tube side to produce flue gases which in turn flow countercurrently and react in the shell side to yield reforming products. The methane conversion reaches 97% at 700oC with the catalyst spray-coated tube, while the catalyst dip-coated tube reaches only 7.78%. Turnover frequencies (TOF) using the catalyst sprayed and dip-coated tubes are 5.75 x 10-5 and 2.24 x 10-5 mol/gram cat.s, respectively. The hydrogen to carbon monoxide ratios produced are greater than the stoichiometric ratio, which are probably caused by carbon deposit through methane cracking and Boudouard reactions.